SIMULATIONS IN TECHNOLOGICAL ENVIRONMENTS AS A TOOL FOR TRAINING IN TRANSVERSAL COMPETENCES FOR UNIVERSITY STUDENTS - Mercè Gisbert Cervera; José M. Cela-Ranill; Sofia Isus Barado (Ediciones Universidad de Salamanca, 2010)
<!-- @page { margin: 0.79in } P { margin-bottom: 0.08in } --> This paper consists of a reflection on how the technological environments can play a key role in the current Higher Education scene. This reflection observes the structural configuration and the key agents of the educational process. The content is developed firstly locating the student in the University of the 21st century; the methodological renovation is analyzed from two perspectives: the development of the technologies and the new role of teacher and student in this new scene; finally the simulations in technological environments are proposed as a valuable strategy to give response to the formative needs of the student in the current society.